Evaluasi Keberhasilan Penanganan Scale Problem Dengan Metode Acidizing di Sumur “Jose-1” Pada Lapangan “Ma-Mandar” Untuk Meningkatkan Laju Alir Produksi - Aldi, Muhammad; Afifah, Rohima Sera; Firdaus, Firdaus; Battu, Desianto Payung; Laby, Dharma Arung; Mustagina, Amanda (DAS Institute, 2021)
Productivity or commonly called productivity index (PI) in a well will decrease. Marked by a decrease in reservoir pressure (Pr), well flowing pressure (Pwf) and rate (Q) in the